1991
DOI: 10.1007/bf00405146
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anti-inflammatory therapy on bacterial clearance following intramammary Escherichia coli challenge in goats

Abstract: Coliform mastitis in dairy cattle frequently results in systemic disease with occasional deaths in association with endotoxic shock. Systemic anti-inflammatory therapy has been used to alter the course of endotoxic shock in severe cases. Use of anti-inflammatory therapy has been questioned on the basis that such treatment may compromise immune function and decrease clearance of bacteria from infected mammary glands. The purpose of this investigation was to determine whether anti-inflammatory therapy influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…[1,19,13]) and its pharmacokinetic properties has been studied in cattle [8,12], sheep [18,2], camels [14,16] and llamas [9]. …”
Section: Introductionmentioning
confidence: 99%
“…[1,19,13]) and its pharmacokinetic properties has been studied in cattle [8,12], sheep [18,2], camels [14,16] and llamas [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Flunixin meglumine and PBZ have been used widely for their antiinflammatory and analgesic properties to treat musculoskeletal conditions and colic in equine practice (Lees & Higgins, 1985). They are also used routinely in ruminant veterinary practice, in the treatment of acute mastitis, endotoxaemia and calf pneumonia in cattle and goats (Anderson et al ., 1986, 1991; Lohuis et al ., 1989), and FM was used to treat endotoxin‐induced reticulorumen stasis and tachycardia in cattle (Eades, 1993). The studies in our laboratory in carrageenan‐induced hyperalgesia have demonstrated that FM is a potent analgesic in sheep (Welsh & Nolan, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This may be valid in cows, where mastitis is often caused by coliforms; these organisms exert their pathogenic action by releasing endotoxin, the effects of which are minimized by flunixin. In a study in which mastitis was induced in goats and treated with flunixin administration alone, no significant differences were observed between treated and control does (Anderson et al, 1991). Caprine mastitis is caused principally by staphylococci and only rarely by coliforms (Bergonnier & Berthelot, 2003 3 ; ; therefore, flunixin should be given simultaneously with an antimicrobial drug effective against the causative agent, as suggested by the results of this study.…”
mentioning
confidence: 65%
“…This may be valid in cows, where mastitis is often caused by coliforms; these organisms exert their pathogenic action by releasing endotoxin, the effects of which are minimized by flunixin. In a study in which mastitis was induced in goats and treated with flunixin administration alone, no significant differences were observed between treated and control does (Anderson et al. , 1991).…”
Section: Description Of Local and Systemic Reaction Scoresmentioning
confidence: 99%